ASSOCIATION ORAL CORTICOSTEROIDS AND LONG-TERM RISK OF CATARACT: A SYSTEMATIC REVIEW AND META-ANALYSIS STUDY - Yovita,; Setiohadji, Bambang (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Cataracts are a significant health concern, particularly in aging populations, impacting vision, mental well-being, and overall quality of life. Corticosteroid use has been linked to cataract development. This study aims to explore the relationship between oral corticosteroid (OCS) exposure and the long-term risk of cataract. Method: Following PRISMA guidelines, a systematic review and meta-analysis were conducted to investigate this association. Relevant studies were identified through comprehensive searches across multiple databases. Data included cataract incidence/prevalence and OCS therapy. Results: A total of 1,270 articles were retrieved from online databases (PubMed, SagePub, SpringerLink and Google Scholar). After three rounds of screening, five articles directly relevant to the systematic review were selected for full-text reading and analysis. These five studies collectively involved 27,250 cases of cataract following oral corticosteroid (OCS) exposure, while 47,267 controls did not develop cataracts. No statistically significant association is found between OCS and cataract formation (OR 0.117, CI 95 0.0085 to 1.6021, p0.11). Conclusion: Cataracts in oral corticosteroid (OCS) users result from abnormal lens cell movement and protein composition changes due to protein adduct formation. Increased OCS dosage and frequency correlate with higher cataract risk. However, evidence quality was deemed low to moderate, highlighting the need for well-designed RCTs to minimize bias and heterogeneity.